Becoming a professional supervisor: Doctoral supervisors’ development in a mandatory, large-scale development programme - Fossland, Trine (Journal of Praxis in Higher Education, 2023)
High-quality supervision is crucial for doctoral researchers’ progression, attrition rates, well-being, and experience of their doctoral journeys. New requirements in higher education have actualised the professional development of doctoral supervisors’ praxis, both as an institutional responsibility and academic field. However, there is a lack of literature exploring doctoral supervisors’ perspectives on professional development. This paper explores what doctoral supervisors find essential for their professional development when attending a mandatory programme for doctoral supervisors. Drawing on a longitudinal case study on the professional development of supervisors, five core aspects essential for the professional development of doctoral supervisors’ praxis are identified: institutional responsibility and support; transformational learning; building a broader repertoire of approaches to supervision; learning to balance complexity, and interaction and identity formation within supervisors’ communities. Based on these findings, a set of institutional recommendations for the professional development of doctoral is suggested.